Community interpreting: breaking with the ’norm’ through normalisation - Toledano, Carmen (The Journal of Specialised Translation, 2010)
In this paper the concept of norm, that has been widely applied in Translation Studies, has been extended to the field of Community Interpreting. From this approach, community interpreting is explained in relation to the socio-historical contexts in which it takes place and the normative framework that shapes it. We also explore how the current situation of de-regularisation affecting this activity in many countries hinders the development of a specific norm framework for community interpreting and as such its consolidation as an independent discipline. Not only that, it also affects the very nature of the activity as interpreter's performance and product is defined by norms and values held by other agents involved in interpreter-mediated encounters. In these cases universities can play a very important role as a norm-setting authority by providing research, training and informative activities.